Uma visão local de um projeto nacional: o curso mídias na educação - Bento, Maria Dalvaci (2011)
The essay "A local view of a national project: the course in Media Education" presents a research aimed at analyzing how the course Media in Education is being implemented by both Federal University of Rio Grande do Norte and State University of Rio Grande do Norte, with the intention of pointing out weaknesses in its use, which should be resolved in order to contribute to the design of other courses along these lines. Therefore, we performed a survey in which data collection, have used open questionnaires available in online pages created specifically for this purpose and administered to alumni and former participants, course participants and tutors from the two universities involved in the research. Through these questionnaires, we identified, especially, those aspects that negatively affect the provision of course related to the student's profile, the virtual learning environment where the course is hosted, the meetings, the contents and activities, the mentoring and the dropout, and the changes to improve the implementation of the course. The research collaborators are professors of public basic education. To understand the continuing education of teachers, conducted through distance education, using the virtual learning environment, we contextualize this from the nineties, in the context of the Brazilian educational reform took place in that decade. The Media in Education course is presented as a different proposition because it allows teachers to follow different pathways, materialized in the learning cycle. At the end of the study, we conclude that the implementation of this course, of the RN, the conditions for dialogue to happen, specifically, are not given